EIB Working Paper 2022/04 - Investment expectations by vulnerable European firms - European Investment Bank (2022)
"The sudden onset of the COVID shock has left European economies reeling, resulting in a sudden contraction of demand that has hit some vulnerable firms and sectors in a remarkably uneven way. There is a genuine interest from policymakers to learn about which types of firms have been left in vulnerable circumstances as a result of the crisis. In this paper, we present new evidence on the evolution of investment plans of certain groups of firms suspected of being vulnerable -young and small firms, High-Growth Enterprises (HGEs) and R&D investors. We applied a difference-in-differences approach on panel data regarding forward-looking investment expectations. The results show that all the vulnerable groups are pessimistic about the availability of internal and external finance, with HGEs suddenly expecting less of a positive change in investment, and R&D investors expecting a negative change in investment."